Screening of Chronic Kidney Diseases in Patients Hospitalized for Surgery at the National Hospital of Zinder in Niger - Hassane Diongolé; Hassan Maman Laouel; Amadou Magagi; Abdoul Aziz Garba; Zeinabou Maiga Moussa Tondi; Laouali Chaibou; Saadatou Brah Waziri; Abdoulaye Idrissa Abdoulmadjid; Lionel Rostaing (Liaquat National Journal of Primary Care)
Background: Chronic kidney diseases (CKD) represent a significant public health issue worldwide, particularly in developing countries. Often with a silent onset, kidney diseases are frequently diagnosed late, necessitating hemodialysis treatment. Hence, prevention through screening remains the primary approach to addressing this issue. Objective: To screen for CKD patients hospitalized at the National Hospital of Zinder, Niger (HNZ) and scheduled for surgery. Methods: This cross-sectional study was conducted within 8 surgical departments of the National Hospital of Zinder (HNZ) in Niger over six months. The study included patients scheduled for surgery across various departments of HNZ. Results: During this period, 497 patients were screened leading to the identification of 91 cases of CKD (stage 3 and below), representing a prevalence of 18.3%. Among the children tested, 33 out of 47 (70.2%) had CKD stage 3 and above, without proteinuria. The mean age of all patients was 31± 8 years, with a gender ratio of 2.6. Medical histories revealed high blood pressure (n=24;4.8%), diabetes (1 patient), urinary tract infections (n=13;2.6%), and obstructive syndrome of the lower urinary tract (n=30;7.8%). Overweight was observed in 4.8% of cases. De novo high blood pressure was identified in 98 patients (24.7%). Dipstick screening yielded positive results in 17 patients (3.4% of cases). Renal ultrasound examination was performed in 75(15.1%) patients, with hydronephrosis being the most frequent finding (n=22, i.e., 29.3% of tested patients). Regarding the absolute number of patients, among the different departments of surgery, CKD prevalence was higher in general surgery, urology, and pediatric surgery. Conclusion: Our findings demonstrate that childhood, hypertension, and urological pathologies are risk factors for CKD. Subclinical renal abnormalities can be detected through screening via urine dipstick urinalysis, biological examinations, and renal ultrasound.